Diario social di un Rettore 2 Appunti di viaggio per un'idea di Università - Dei, Luigi (Libere carte, 2017)
Don Carlos Galvèz's dream could very well be a dream of Maestro Manzi. Luigi Dei's book is dedicated to a public school that believes in children, gives value to teachers and wants to wake up every morning to rediscover the world from scratch. (Centro Alberto Manzi) A true homage to teaching and the need for quality public education. A collection of thoughts and ideas formulated as ad hoc quotes, poems and operettas. Suggestions for the re-evaluation of research in Italy: a project in which we are actively engaged. (AIRIcerca - International Association of Italian Researchers) A window on the Italian scene painted by those who live it every day. Travel notes but also concrete proposals to improve research in our country, perfectly in line with our objectives. (Tempesta di Cervelli)